Islamic Psychological Methodology: A Review of the Literature - Mela Desina; Vivik Shofiah; Khairunnas Rajab (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study explores the methodological framework of Islamic psychology, which integrates scientific approaches with Islamic values as its epistemological foundation. The employed methods extend beyond empirical and rational inquiry by incorporating faith-based approaches grounded in the Qur’an and Hadith, as well as intuitive and spiritual dimensions that are distinctively Islamic. The study examines several methodological orientations—namely scripturalist, philosophical, and Sufi approaches—in an effort to construct a holistic and authentic paradigm of psychology. The purpose of this research is to develop a methodological framework for Islamic psychology that is both epistemologically valid and practically applicable, accommodating both spiritual and scientific dimensions while offering psychological solutions consistent with Islamic principles. This research adopts an extensive literature review of both classical and contemporary sources on Islamic psychology. The findings reveal that the methodological framework of Islamic psychology has the potential to enrich the broader field of psychology through a comprehensive, integrative, and contextually responsive approach that addresses the psychological needs of the Muslim community.